Development Of A Career Exploration Module To Enhance Career Decision-Making In Vocational Teacher Education - Khojanatun, Khojanatun; Kusumastuti, Adhi; Ihsani, Ade Novi Nurul (Universitas Negeri Semarang, 2025)
This study developed a career exploration module embedded within the Ethics and Teaching Profession course to help vocational students make thoughtful and informed career decisions. Many students in the Informatics and Computer Engineering Education (PTIK) program often feel uncertain about pursuing a teaching career or entering the technology sector. The module included structured reflection and value-based activities to help students align their personal goals with professional paths. Using the ADDIE model—Analyze, Design, Develop, Implement, and Evaluate—the researchers implemented the module with sixth-semester PTIK students at Institut Prima Bangsa Cirebon. Experts validated the content and media, and classroom trials measured its practicality and impact. Findings showed improved students’ ability to recognize their values, explore options, evaluate consequences, and make responsible choices. As a result, students gained greater confidence and clarity in their career planning, reduced indecision, and demonstrated more substantial alignment between their choices and long-term aspirations. The module supported ethical, realistic, and goal-driven decision-making.